Photonic hook shaping achieved by the micro-nano fiber array based Janus cylindrical metalens - Dinh Quoc-Thinh; Wu Yi-Cin; Chen Wei-Yu; Chen Yu-Bin; Minin O. V. Oleg Vladilenovich; Minin I. V. Igor Vladilenovich; Liu Cheng-Yang (2024, 2024)
Title screen